Metabolic Games - Pusa, Taneli; Wannagat, Martin; Sagot, Marie-France (Frontiers in Applied Mathematics and Statistics, 2019)
Metabolic networks have been used to successfully predict phenotypes based on optimisation principles. However, a general framework that would extend to situations not governed by simple optimisation, such as multispecies communities, is still lacking. Concepts from evolutionary game theory have been proposed to amend the situation. Alternative metabolic states can be seen as strategies in a "metabolic game", and phenotypes can be predicted based on the equilibria of this game. In this survey, we review the literature on applying game theory to the study of metabolism, present the general idea of a metabolic game, and discuss open questions and future challenges.